Spatial Distribution of Invasive Alien Plant Species in Baglung and Kushma Municipalities, Central Nepal (Himalayan Biodiversity, 2025)
Invasive alien plant species (IAPs) frequently find ideal small-scale habitats in urban settings, where they can grow and spread their seeds throughout the environment around them. In addition to offering possibilities for early identification and elimination of invaders, regular monitoring of IAPs in urban areas produces science-based data for the management of IAPs. In this study, we inventoried IAPs and documented their spatial distribution in Baglung and Kushma municipalities, central Nepal. We evaluated the flora along the sides of the roadways in 80 plots (5 × 5m2) spaced out across the roads in municipalities at intervals of roughly 500 m using a checklist of the 27 IAPs that have been recorded from Nepal. The IAPs present in each plot were noted together with the location's coordinates. The frequency and distribution maps of the IAPs were prepared using field data. ArcGIS was used to prepare distribution maps for each IAP and the general distribution patterns for species richness. In Bagiung and Kushma municipalities, we recorded eleven IAPs, i.e. 43% of the total number of IAPs recorded from Nepal. Bidens pilosa had the highest frequency,  whereas Galinsoga quadriradiata had the lowest. Two of the recorded IAPs, Chromolaena odorata and Lantana camara, were among 100 of the world’s worst invasive species. IAPs have been spreading quickly over road networks in Kushma and Baglung. IAPs distribution and periodic inventories are therefore to be thoroughly carried out at the national level to establish management methods for preventing biological invasion.